2012
DOI: 10.1002/ana.23568
|View full text |Cite
|
Sign up to set email alerts
|

Somatic mitochondrial DNA mutations in early parkinson and incidental lewy body disease

Abstract: Somatic mutations in mitochondrial DNA (mtDNA) are hypothesized to play a role in Parkinson disease (PD), but large increases in mtDNA mutations have not previously been found in PD, potentially because neurons with high mutation levels degenerate and thus are absent in late-stage tissue. To address this issue, we studied early stage PD cases and cases of incidental Lewy body disease (ILBD), which is thought to represent presymptomatic PD. We show for the first time that mtDNA mutation levels in substantia nig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
2
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(87 citation statements)
references
References 22 publications
7
77
2
1
Order By: Relevance
“…Alternatively, the discordance between our findings and earlier reports could be explained by their use of PCR based assays, which can lead to erroneous misincorporation events, to quantify mutations. Consistent with this possibility is that the mutation frequencies we report here are ~10-fold lower than those reported in these studies, 5, 23 and are in closer agreement with previous studies in humans. 6 …”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Alternatively, the discordance between our findings and earlier reports could be explained by their use of PCR based assays, which can lead to erroneous misincorporation events, to quantify mutations. Consistent with this possibility is that the mutation frequencies we report here are ~10-fold lower than those reported in these studies, 5, 23 and are in closer agreement with previous studies in humans. 6 …”
Section: Discussionsupporting
confidence: 94%
“…23 This striking contrast points to an underlying difference in the etiologies of AD and PD and suggests that, unlike early PD, mitochondrially localized oxidative stress may not be an early contributor to AD. Alternatively, the discordance between our findings and earlier reports could be explained by their use of PCR based assays, which can lead to erroneous misincorporation events, to quantify mutations.…”
Section: Discussionmentioning
confidence: 99%
“…MPTP also is of interest because it selectively damages dopaminergic neurons, and accidental human exposure to MPTP can cause clinical features similar to Parkinson’s disease (PD) (Langston et al, 1983; Langston 1996). We recently reported that substantia nigra (SN) neurons accumulate very high levels of somatic mtDNA mutations during early stages of PD, similar in some neurons to levels demonstrated to cause functional impairment in the POLG mut/mut mice (Lin et al, 2012). At older ages, POLG mut/mut mice demonstrate significant reductions in striatal dopaminergic terminals as well as deficits in motor function compared to wild type (WT) littermates (Dai et al 2013).…”
Section: Introductionmentioning
confidence: 88%
“…The underlying pathogenic mechanisms are not well understood, although a growing body of research suggests mitochondrial respiratory dysfunction and oxidative stress contribute to disease pathogenesis [62][63][64][65]. In some Parkinson's disease patients, mtDNA mutations have also been detected, specifically in the D-loop region and the MT-ND5 gene [65]. …”
Section: Oxphos Complex Imentioning
confidence: 99%